2022
DOI: 10.3390/jcm11143979
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Relapse in Patients with Bipolar Disorder

Abstract: Pregnancy and postpartum are vital times of greater vulnerability to suffer a decompensation of bipolar disorder (BD). Methods: A systematic literature search was performed on public electronic medical databases, following PRISMA guidelines. Studies were included if they reported postpartum relapse in patients diagnosed with BD according to Diagnosis Statistical Manual (DSM) or International Classification Disease (ICD) criteria. Results: Sixteen articles describing 6064 deliveries of 3977 women were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Another systematic review found a relapse risk of 36.7% in 3977 women with 6064 deliveries. 5 Finally, a recent systematic review and meta-analysis estimated that 54.9% (95% CI, 39.2-70.2) of women with pre-existing illness had at least one bipolar-spectrum mood episode during pregnancy or 1 month postpartum. 6 Depression is the most common condition postpartum in studies considering all types of bipolar disorder, 5 however, studies reporting the specific types of bipolar disorder have found a greater prevalence of mania or postpartum psychosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review found a relapse risk of 36.7% in 3977 women with 6064 deliveries. 5 Finally, a recent systematic review and meta-analysis estimated that 54.9% (95% CI, 39.2-70.2) of women with pre-existing illness had at least one bipolar-spectrum mood episode during pregnancy or 1 month postpartum. 6 Depression is the most common condition postpartum in studies considering all types of bipolar disorder, 5 however, studies reporting the specific types of bipolar disorder have found a greater prevalence of mania or postpartum psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…5 Finally, a recent systematic review and meta-analysis estimated that 54.9% (95% CI, 39.2-70.2) of women with pre-existing illness had at least one bipolar-spectrum mood episode during pregnancy or 1 month postpartum. 6 Depression is the most common condition postpartum in studies considering all types of bipolar disorder, 5 however, studies reporting the specific types of bipolar disorder have found a greater prevalence of mania or postpartum psychosis. 5,[7][8][9][10] With the publication of its fourth edition in 1994, the Diagnostic and Statistical Manual first acknowledged the heightened risk of manic, mixed, and depressive episodes after delivery.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, the perinatal period can negatively impact maternal mental health. [1][2][3] Women with previous psychiatric disorders such as psychotic, bipolar, and depressive disorders have a considerable risk of relapse in the peripartum period. 1,2,4,5 Moreover, studies also established severe maternal and neonatal adverse consequences.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Women with previous psychiatric disorders such as psychotic, bipolar, and depressive disorders have a considerable risk of relapse in the peripartum period. 1,2,4,5 Moreover, studies also established severe maternal and neonatal adverse consequences. [6][7][8] Mothers with psychiatric disorders are at higher risk of admission to an intensive care unit, unplanned cesarean section, gestational diabetes, preeclampsia, induced labor, and have lower rates of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation